Application of new oxidoreductases in bleaching of kraft pulp - Silva, Andreia de Freitas (2018)
Pulp bleaching is one of the most important and expensive processes in the pulp and paper industry. Along the years this technology has gone through several changes in order to reduce the ecological risks and the production costs. The aim of this work is to study the application of a new oxidoreductase, produced by Novozymes A/S, in ECF and TCF bleaching of oxygen pre-bleached Eucalyptus kraft pulp and then to compare the bleaching performance of this enzyme with other oxidoreductases already studied or commercialized by the company. The oxidoreductase used in this study was primarily the NS-51002 laccase (and its variants) of which culture broths were purified. The laccase-mediator system and the incubation conditions were optimized. Then the NS-51002 laccase bleaching performance was compared with other enzymes like Novozym 51003 laccase and NS-51004 and NS-51113 peroxidases. The best enzyme proved to be the NS-51113 peroxidase, which was also optimized in terms of application conditions. Besides the enzymatic stages, the dosage of chemical used in the alkaline extraction stage was also optimized. Afterwards, the NS-51002 laccase and the NS-51113 peroxidase were implemented in several ECF and TCF bleaching sequences. To study the effect of the enzymes and chemicals on bleaching a number of properties were measured in different parts of the sequence, such as: ISO brightness; kappa number; hexenuronic acid content; viscosity; pH, residual hydrogen peroxide and COD in the pulp filtrates. Using the sequence DEpDP (90,5%) as reference, it was concluded that the implementation of an enzymatic stage with xylanase in the beginning of the sequence, i.e. XDEpDP (91,1%), enhanced the pulp brightness. Furthermore, some sequences using the NS-51113 peroxidase as the L stage proved to be quite effective from the bleaching point of view, allowing to reach 90±0,5 of ISO brightness, in particular the sequence XLEpDP (89,5%).